2019
DOI: 10.1017/s0007114519003027
|View full text |Cite
|
Sign up to set email alerts
|

Crude extract of Camellia oleifera pomace ameliorates the progression of non-alcoholic fatty liver disease via decreasing fat accumulation, insulin resistance and inflammation

Abstract: Consumption of a high-fat diet increases fat accumulation and may further lead to inflammation and hepatic injuries. The aim of the study was to investigate the effects of Camellia oleifera seed extract (CSE) on non-alcoholic fatty liver disease (NAFLD). After a 16-week NAFLD-inducing period, rats were assigned to experimental groups fed an NAFLD diet with or without CSE. At the end of the study, we found that consuming CSE decreased the abdominal fat weight and hepatic fat accumulation and modulated circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Plants and their bioactive compounds may have significant positive effects on MAFLD due to their numerous pharmacological effects [ 53 ]. Several studies have demonstrated that certain tea extracts such as Liupao tea extract [ 54 ]; epigallocatechin gallate [ 55 ]; pentoxifylline [ 56 ]; Camellia oleifera seed extract [ 57 ]; flavonoid compounds such as didymin [ 58 ], chrysin [ 59 ], luteolin [ 60 ] and Tremella fuciformis crude polysaccharides [ 61 ]; black ginseng [ 62 ], Rhodomyrtus tomentosa (Ait.) husk fruit phenolic rich extract [ 63 ]; and thyme polyphenol-rich extract [ 64 ] could reduce IR, improve intestinal microecology, and mitigate MAFLD progression by downregulating TLR4/MyD88/NF-κB signaling pathway transduction and reducing TNF-α, IL-6, and TGF-β levels.…”
Section: Therapeutic Strategies For Mafld Targeting Tlr4 Signaling Pa...mentioning
confidence: 99%
“…Plants and their bioactive compounds may have significant positive effects on MAFLD due to their numerous pharmacological effects [ 53 ]. Several studies have demonstrated that certain tea extracts such as Liupao tea extract [ 54 ]; epigallocatechin gallate [ 55 ]; pentoxifylline [ 56 ]; Camellia oleifera seed extract [ 57 ]; flavonoid compounds such as didymin [ 58 ], chrysin [ 59 ], luteolin [ 60 ] and Tremella fuciformis crude polysaccharides [ 61 ]; black ginseng [ 62 ], Rhodomyrtus tomentosa (Ait.) husk fruit phenolic rich extract [ 63 ]; and thyme polyphenol-rich extract [ 64 ] could reduce IR, improve intestinal microecology, and mitigate MAFLD progression by downregulating TLR4/MyD88/NF-κB signaling pathway transduction and reducing TNF-α, IL-6, and TGF-β levels.…”
Section: Therapeutic Strategies For Mafld Targeting Tlr4 Signaling Pa...mentioning
confidence: 99%
“…Camellia oleifera is one of four major woody oil plants in the world, and its seed oil enjoys the reputation of “Oriental olive oil” because of its similar fatty acid composition to that of olive oil in Europe. Camellia oil is rich in various bioactive ingredients, and long-term intake of camellia oil can regulate immune function; decrease cholesterol levels; lower blood sugar and lipids; and prevent hypertension, hepatic, cardiovascular, and neurological diseases [ 21 , 22 , 23 ]. Moreover, it has strong antioxidant activity and high thermal stability after refining; its good affinity to human skin can help to improve skin conditions and even reduce skin aging [ 24 , 25 , 26 ].…”
Section: Woody Oil Plant Resources In Chinamentioning
confidence: 99%
“…With the changes in lifestyles and dietary patterns, the prevalence of NAFLD affects one-quarter of the population around the world [6]. Mounting evidence demonstrated that NAFLD subjects are at higher risk of developing serious metabolic-related diseases [7], as people with NAFLD frequently coexist with insulin resistance (IR) related diseases such as abnormal glucose tolerance, lipid metabolism disorder and hypertension [8,9]. Thus, it is a crucial public health problem in the prevention and management of NAFLD [10].…”
Section: Introductionmentioning
confidence: 99%